2017
DOI: 10.1155/2017/2409062
|View full text |Cite
|
Sign up to set email alerts
|

Spreadability of Ag Layer on Oxides and High Performance of AZO/Ag/AZO Sandwiched Transparent Conductive Film

Abstract: Single layers of indium tin oxide (ITO), aluminum-doped zinc oxide (AZO), and Ag, bilayers of ITO/Ag and AZO/Ag, and sandwiched layers of ITO/Ag/ITO (IAI) and AZO/Ag/AZO (ZAZ) were fabricated on ordinary glass substrates using magnetron sputtering. The surface morphologies of single layers and bilayers were measured. The sheet resistance and transmittance of the sandwiched layers were investigated. The results showed that the spreadability of the Ag on the AZO was significantly better than that on the ITO or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The reduction in transmittance in the NIR region is recognized to the scattering by free electrons and metallic surface. 28,29 It is documented that the optical transmittance is intensely associated with the charge carrier concentrations. Therefore, the decrease in the optical transmittance is endorsed to the increase in carrier concentrations as the Cu interlayer thickness increased.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in transmittance in the NIR region is recognized to the scattering by free electrons and metallic surface. 28,29 It is documented that the optical transmittance is intensely associated with the charge carrier concentrations. Therefore, the decrease in the optical transmittance is endorsed to the increase in carrier concentrations as the Cu interlayer thickness increased.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were reported for bilayer Ag(8 nm)/AZO (3 wt% Al doped ZnO) on soda lime glass substrate in Ref. On the other hand, the Ag/Ti/AZO/glass and Ag/Nb/AZO/glass structures had also a lower electrical sheet resistance, as seen in Table . These results showed that the grown film with M‐Seed is a continuous film without island formation.…”
Section: Resultsmentioning
confidence: 99%
“…In case low emissivity coatings on glass, generally, thin silver layer was sandwiched between two dielectric layers such as dielectric/Ag/dielectric such as AZO/Ag/AZO . Conductivity of Ag film correlated with optical properties has main role on emissivity of the film stacks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a lot of studies in the literature about the properties of multiple tri-layer structures (dielectric/metal/dielectric) with different dielectric materials: SnO 2 [32,33], ZnO [34][35][36][37][38], AZO (aluminum-doped zinc oxide) [39][40][41][42][43][44], ITO (tin-doped indium oxide) [45,46] (AZO and ITO are semiconductor materials but they fulfil an optical dielectric function in this type of structure), ZnS [47,48], TiN [49,50], TiO 2 [51], TiAlN (Al-doped titanium nitride) [52], AlN [53], and SiN [19,54]. Furthermore, comparative studies have also been conducted among some of them [55][56][57][58][59]. Each of these materials has its advantages and disadvantages for industrial use.…”
Section: Introductionmentioning
confidence: 99%